The Cell and the Sum of Its Parts: Patterns of Complexity in Biosignatures as Revealed by Deep UV Raman Spectroscopy - Sapers, Haley M.; Razzell Hollis, Joseph; Bhartia, Rohit; Beegle, Luther W.; Orphan, Victoria J.; Amend, Jan P. (Frontiers in Microbiology, 2019)
The next NASA-led Mars mission (Mars 2020) will carry a suite of instrumentation dedicated to investigating Martian history and the in situ detection of potential biosignatures. SHERLOC, a deep UV Raman spectrometer has the ability to detect and map the distribution of organic molecules in low concentrations, including some that are known to be fundamental building blocks of life on Earth. The mere presence of organic compounds is not a biosignature: there is widespread distribution of reduced organic molecules in the Solar System. Life utilizes a select few of these molecules creating conspicuous enrichments of specific molecules that deviate from the distribution expected from purely abiotic processes. The detection of far from equilibrium concentrations of a specific subset of organic molecules is thought to be a universal biosignature independent of specific terrestrial biochemistry. The detectability and suitability of a small subset of organic molecules to adequately describe a living system is explored using the bacterium Escherichia coli as a model organism. The DUV Raman spectra of E. coli cells are dominated by the vibrational modes of the nucleobases adenine, guanine, cytosine, and thymine, and the aromatic amino acids tyrosine, tryptophan, and phenylalanine. We demonstrate that not only does the deep ultraviolet (DUV) Raman spectrum of E. coli reflect a distinct concentration of specific organic molecules, but that a sufficient molecular complexity is required to deconvolute the cellular spectrum. Furthermore, a linear combination of the DUV resonant compounds is insufficient to fully describe the cellular spectrum. The residual in the cellular spectrum indicates that DUV Raman spectroscopy enables differentiating between the presence of biomolecules and the complex uniquely biological organization and arrangements of these molecules in living systems. This study demonstrates the ability of DUV Raman spectroscopy to interrogate a complex biological system represented in a living cell, and differentiate between organic detection and a series of Raman features that derive from the molecular complexity inherent to life constituting a biosignature.